RELATIONSHIP BETWEEN INFLATION MEASURED IN WHOLESALE PRICE INDEX (WPI) AND MOVEMENT IN INDIAN EQUITY MARKET - Biswas, Tapas; Mishra, Dr. Ajit Kumar (IJRDO - Journal of Business Management, 2017)
This study is an attempt to understand the impact of Inflation (wholesale price index)on Indian capital market (BSE Sensex). For empirical estimation, this study has usedmonthly average data for the both the series for the period covering from April 2005 to March 2016. The study has used econometrics techniques such as AugmentedDickey Fuller Test, Johansen’s Cointegration Test and Granger Causality Test. Thefindings of the empirical estimations suggest that there is a cointegrating relationshipbetween WPI and BSE Sensex indicating a long-run relationship between both thevariables. However, the Granger Causality test reveals that there is no causalrelationship between BSE Sensex and WPI Inflation in the short run.